Practice Of Self Medication Among Urban Households –A Community Based Cross Sectional Study - Chari, Harini S; Kadeangadi, Deepti M; Mallapur, M D (National Journal of Community Medicine, 2015)
Introduction: Reckless use of Self- medication poses a threat for both individual health and society. In India, prevalence was esti- mated to be 31% but there is a wide variation within the country. The aim of this study was to know the practice of self-medication and contributory factors among households of an urban area. Methods: This study was done based on primary data. Primary data was collected from about 200 households residing in Bela- gavi. The households were selected using systematic random sampling technique. Data was collected using a predesigned structured oral questionnaire. Statistical analysis was done using Percentages after entering the data in Microsoft excel sheet. The association between self-medication and socio-demographic fac- tors was ascertained using Chi–square test. Results: The results found that the overall prevalence of self- medication was 35.1%. Paracetamol (90.9%) was the most com- monly used drug. Headache (98.6%) and fever (47.1%) were the most common symptoms for the practice of self-medication. Common reason quoted for self-medications was minor illness (78.8%) and sources for self-medication were either previous pre- scriptions (51.4%) or local pharmacists (25.5%). Conclusions: One-third of the subjects practiced self-medication. Self-medication was more common among women and the higher socio-economic strata.